Sustainability and Society: Do Environmental, Social, and Governance Factors Matter for Foreign Direct Investment? - Niranjan Chipalkatti; Quan Vu Le; Meenakshi Rishi (Energies, 2021)
Sustainable investing allocates investments based on environmental, social and governance factors (ESG). The societal value of sustainable investment is becoming progressively relevant as investors are increasingly recognizing the importance of investing in companies that seek to combat climate change, environmental destruction, while promoting corporate responsibility. Environmental policy and sustainable growth initiatives at a country-level are also being influenced by the UN’s Sustainable Development Goals (SDGs). Situated within the current trend of declining foreign direct investment flows (FDI), our study examines the role of ESG factors in attracting FDI and enabling progress toward SDGs. We econometrically examine the linkages between ESG and FDI inflows for a sample of 161 counties. We also focus on low- and middle-income emerging economies and low- and middle-income commodity exporters as these countries face unique challenges of mobilizing financing to achieve SDGs and generating sustainable economic growth. Results suggest that FDI inflows to the full sample of countries are positively attracted by good governance in a destination country. We observe that good scores on HDI deters FDI, that higher FDI flows are associated with higher levels of carbon emissions in the case of emerging markets. Sustainability reporting attracts FDI to commodity exporting countries. The study provides possibilities for future research in a post-pandemic future.